Role and Impact of Safety Leadership Culture in Promoting Safety Practices in Construction Sector of Pakistan - Mohtashim Khaqan, Qureshi; Muhammad Inam, Abbas; Ghassan, Husnain; Faizan, Farid; Muhammad Waleed, Sarwar; Ijaz, Ahmad (INTI International University, 2024)
The construction industry offers employment to about one hundred eighty million people worldwide. The construction sector has grown and evolved to meet the demands of urbanization and industrialization, which are the foundation of the modern economy. Construction is still seen as a risky and difficult industry, with the most hazardous and vulnerable work environment, even with the industry's notable improvements. Pakistan's construction industry is known for its high level of risk, which makes strict safety procedures necessary to protect the health and safety of its workforce. This research seeks to understand the impact of safety leadership on safety practices and identify key factors influencing safety culture. In order to provide comprehensive insights, the research uses a mixed-methods approach that combines quantitative surveys and qualitative interviews. The validity and reliability of the results are ensured by thorough experimentations of the statistical methods such as reliability test, relative importance index (RII), and descriptive analysis tests. In order to effectively promote safety practices, management commitment, employee involvement, safety training, and good communication are essential. An in-depth examination of the relationship between management commitment and safety performance reveals how effective leadership and proactive participation improve safety results. The results shows that safety leadership is crucial to encourage safety procedures in Pakistan's construction sector by 68.81%, success factor for safety management by 65.42%, safety management practices by 64.32%, safety performance by 63.35%, barriers to effective safety management 62.47% and safety culture by 61.46%. Strengthening frameworks for regulations, promoting a safety-first culture, investing more in safety equipment, improving worker safety training, improving monitoring and evaluation mechanisms, fostering communication and collaboration, and addressing cultural barriers are just a few of the recommendations.